2021
DOI: 10.1530/vb-21-0007
|View full text |Cite
|
Sign up to set email alerts
|

microRNAs involved in psoriasis and cardiovascular diseases

Abstract: Psoriasis is a chronic inflammatory disease involving skin. Both genetic and environmental factors play a pathogenic role in psoriasis and contribute to the severity of the disease. Psoriasis, in fact, has been associated with different comorbidities such as diabetes, metabolic syndrome, gastrointestinal or kidney diseases, cardiovascular diseases (CVD), and cerebrovascular diseases (CeVD). Indeed, life expectancy in severe psoriasis is reduced by up to 5 years due to CVD and CeVD. Moreover, patients with seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 159 publications
(259 reference statements)
0
19
0
3
Order By: Relevance
“…Dos 72 artigos levantados, após análise, exclusão conforme critérios explícitos no método e leitura, resultaram 12 publicações para a amostra final 1,3,5,7,8,12,15,16,18,19,22,23 .…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Dos 72 artigos levantados, após análise, exclusão conforme critérios explícitos no método e leitura, resultaram 12 publicações para a amostra final 1,3,5,7,8,12,15,16,18,19,22,23 .…”
Section: Resultsunclassified
“…Ainda, segundo o mesmo autor, essas cascatas inflamatórias aumentam o estresse oxidativo local tornando as plaquetas menos estáveis. Além disso, a aterosclerose e a psoríase compartilham da resposta inflamatória mediada pelo linfócito TCD4+ helper 1 (Th1), ocorrendo em ambos as alterações da angiogênese e disfunções endoteliais 16 . Também há relatos de que as placas ateroscleróticas e as psoriásicas possuem características histológicas de inflamação e infiltração leucocitária similares.…”
Section: Ateroscleroseunclassified
See 1 more Smart Citation
“…Psoriasis is a chronic inflammatory disorder of skin featuring aberrant keratinocyte proliferation and the production of inflammatory mediators, including pro-inflammatory cytokines; 19 however, the exact pathogenesis of psoriasis remains unclear. Recent studies have identified many dysregulated miRNAs in psoriasis, 20 , 21 and Zhang et al . 22 found that the overexpression of the miR- 17-92 cluster can promote keratinocyte proliferation and immune function and thus may contribute toward the development of psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Psoriasis appears to be an independent risk factor for atherosclerotic CVD, this is probably due to the role that systemic inflammation plays in the induction of premature atherosclerosis and CVD in psoriatic patients ( 31 , 40 ).…”
Section: Discussionmentioning
confidence: 99%